Can upwelling signals be detected in intertidal fishes of different trophic levels?. Issue 5 (11th October 2013) - Pulgar, J.; Poblete, E.; Alvarez, M.; Morales, J. P.; Aranda, B.; Aldana, M.; Pulgar, V. M.
<x xml:space="preserve">Abstract</x> For intertidal fishes belonging to three species, the herbivore Scartichthys viridis (Blenniidae), the omnivore Girella laevifrons (Kyphosidae) and the carnivore Graus nigra (Kyphosidae), mass and body size relationships were higher in individuals from an upwelling zone compared with those from a non‐upwelling zone. RNA:DNA were higher in the herbivores and omnivores from the upwelling zone. Higher biomass and RNA:DNA in the upwelling intertidal fishes may be a consequence of an increased exposure to higher nutrient availability, suggesting that increased physiological conditioning in vertebrates from upwelling areas can be detected and measured using intertidal fishes of different trophic levels.